Values of Gifted Specialists as a Professional Identity - Bailey Nafziger; Seth Kaesler (Georgia Educational Researcher)
Educators of gifted students (gifted specialists) face unique systematic and personal barriers daily. While programs for gifted students are mandated in most states, including Georgia, implementation choices such as identification processes, delivery models, and teacher training requirements often fall on local agencies and budgets. Gifted specialists must have a strong sense of agency to advocate for their students and programs. This study contrasts the values, beliefs, and attitudes of middle-level teachers who have taught in an honors program and gifted specialists with a gifted teacher endorsement or certificate. The two expert groups were established to contrast how teachers who self-identify as gifted specialists compare to teachers with no formal training in the field but who have taught classrooms of primarily gifted students. Qualitative values-coding was used to identify unique perspectives gifted specialists held. Two major themes emerged: (1) the perception of who is responsible for gifted student success and (2) whether gifted students have heterogeneous or homogeneous needs. The authors propose using the values, beliefs, and attitudes as a professional identity model to enhance the agency and retainment of gifted specialists.